Fandom as an online support group : a case study of CW's Supernatural - Tammentie, Bastian (2016)
As online chats and forums became more popular recreational activities it contributed to communities being transferred to cyberspace. Fans have constituted a unique user group from the very beginning of online networking, providing a space for like-minded individuals to bond and build an intercontinental community and to engage in activities related to the object of their affection from producing fan content to taking part in fan-based activism. Peer support and the positive impact of social acceptance have been found to have a positive impact on an individual’s mental well-being while also preventing social isolation. Likewise, social networking has also brought celebrities and fans closer as they are now able to share the same forums in the form of social media platforms, and thus can also be used to promote products, shows, or charity campaigns, sometimes lead by a celebrity with a strong fan following. It is argued that a charity may gain more publicity when supported by an idol, and that when the celebrity has a personal connection to or experience of the issue, the message is made more powerful and believable for the audience. This dissertation aspires to combine the elements of celebrity-driven charities, fan activism and peer support, and studies the personal impact the charity campaigns launched by idols have had on the fans concerned. The research is conducted as a case study of the fandom surrounding the CW network’s cult television series “Supernatural”. The focus is on the charity campaigns campaigning for raising awareness of mental health, above all depression, launched by either or all of the three lead actors, and how the campaigns and celebrity involvement has been received by the fans. These questions are answered as a non-participant study by observing and analysing the comments written by the fans of the show and the actors on the actors’ public Fabebook pages. The dissertation finds celebrity involvement in charity campaigns promoting mental health and raising awareness of mental illnesses to have a positive impact on the fans who themselves suffer from a mental illness and to create a micro-support network within the larger network of the fandom as a whole. The fans with a personal connection to the subject of the campaigns were found to be more likely to consider celebrity involvement in the campaigns as empowering as opposed to fans without such connection, although a negative response to celebrity involvement was found to be rare, although further research is required.